2009
DOI: 10.1002/dneu.20710
|View full text |Cite
|
Sign up to set email alerts
|

Notch activation induces neurite remodeling and functional modifications in SH‐SY5Y neuronal cells

Abstract: Notch proteins are definitely recognized as key regulators of the neuronal fate during embryo development, but their function in the adult brain is still largely unknown. We have previously demonstrated that Notch pathway stimulation increases microtubules stability followed by the remodeling of neuronal morphology with neurite varicosities loss, thicker neuritis, and enlarged growth cones. Here we show that the neurite remodeling is a dynamic event, dependent on transcription and translation, and with functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Analyses of mammalian neurons in a variety of primary culture and cell line paradigms have provided insights into mechanisms by which Notch may control neurite growth [1719]. These include stabilization of microtubules[20], turnover of varicosities and filopodia on neurites, and changes in the expression of a variety of cytoskeletal and signaling proteins that modulate neurite growth[21]. Consistent with in vitro studies, Notch and its ligands are present on both axons and dendrites of mammalian neurons in vivo [22, 23].…”
Section: Direct and Indirect Effects Of Notch On Axon And Dendrite Pamentioning
confidence: 99%
“…Analyses of mammalian neurons in a variety of primary culture and cell line paradigms have provided insights into mechanisms by which Notch may control neurite growth [1719]. These include stabilization of microtubules[20], turnover of varicosities and filopodia on neurites, and changes in the expression of a variety of cytoskeletal and signaling proteins that modulate neurite growth[21]. Consistent with in vitro studies, Notch and its ligands are present on both axons and dendrites of mammalian neurons in vivo [22, 23].…”
Section: Direct and Indirect Effects Of Notch On Axon And Dendrite Pamentioning
confidence: 99%
“…They are regarded as presynaptic, dynamic structures that are able to remodel their morphology in response to a variety of stimuli (De Paola et al, 2003;Nikonenko et al, 2003;Udo et al, 2005;Umeda et al, 2005;Ferrari-Toninelli et al, 2009). Varicosities appear as membrane swellings of various size.…”
Section: Neurite Branching and Varicosities Are Reduced In P50mentioning
confidence: 99%
“…A group of studies over the past decade have provided in vitro evidence for a function of canonical Notch signaling in the regulation of neurite outgrowth in the nervous system [9], [10], [17], [18], [19], [22]; however, our study is the first to use an in vivo model to show that the canonical Notch pathway plays a vital role in axonal growth in the vertebrate nervous system. We found that ectopically expressing NICD in newly differentiated post-mitotic commissural neurons decreased axon midline crossing by about 87% compared to controls, indicating that activation of Notch signaling severely hinders axon outgrowth.…”
Section: Discussionmentioning
confidence: 89%
“…Notch signaling is also known to promote dendritic branching [9], and to inhibit neurite extension in cultured rodent cortical neurons [9], [10], [18], N2a neuroblastoma cells [19] and PC12 cells [20]. Furthermore, in cultured murine cortical neurons and differentiated human SH-SY5Y neuroblastoma cells, Notch signaling can induce microtubule stabilization in neurites and thereby promote neurite outgrowth and branching as well as growth cone enlargement [21], [22]. However, in vivo evidence demonstrating the effects of Notch signaling on axon outgrowth is still lacking.…”
Section: Introductionmentioning
confidence: 99%